2019
DOI: 10.1039/c9ta00074g
|View full text |Cite
|
Sign up to set email alerts
|

Nanocatalysis by noble metal nanoparticles: controlled synthesis for the optimization and understanding of activities

Abstract: This review discusses the importance of physical/chemical control in metallic NPs for the optimization and understanding of catalytic performances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
193
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 275 publications
(196 citation statements)
references
References 129 publications
1
193
0
2
Order By: Relevance
“…For example, porous silica particles find widescale application as catalyst supports (also in nanocomposite catalysts), adsorbents, molecular sieves, chemical sensors, etc. [9][10][11][12][13]. Recent research also found mesoporous silica particles to be very promising medical drug carriers [14].…”
Section: Numerousmentioning
confidence: 99%
“…For example, porous silica particles find widescale application as catalyst supports (also in nanocomposite catalysts), adsorbents, molecular sieves, chemical sensors, etc. [9][10][11][12][13]. Recent research also found mesoporous silica particles to be very promising medical drug carriers [14].…”
Section: Numerousmentioning
confidence: 99%
“…Nanoparticles as a catalyst have recently attracted the attention of the scientific community because of their high selectivity, durability, recoverability with considerable economic benefits in manufacturing as an industrial commodity. [1] Metal nanoparticles as catalysts are popular owing to their high surface area properties, leading to enhanced interaction between reactant and catalyst surface, hence high activities observed even under mild conditions. [2] Nanocatalysts have various applications in numerous fields such as refinery, petrochemicals, pharmaceuticals, chemicals, food processing.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] Due to the high surface to volume ratio, these nanoscale metals, particularly platinum (Pt) and palladium (Pd), are also effective catalysts for various chemical reactions. [ 6 ] To dates, various types of metal nanoparticles (e.g., triangular Au nanoplates, [ 7 ] Ag nanocubes, [ 8 ] and Pt nanoboxes [ 9 ] ) with tunable size and shapes have been successfully synthesized. [ 7,9,10 ] Among them, anisotropic silver nanostructures with sharp corners (e.g., bipyramid) and polyhedral nanocrystals with defined crystallographic facets (e.g., (111) and (100)) are of great importance due to their lower energy loss and stronger electric field, [ 11 ] which are well suited for metal‐enhanced fluorescence (MEF), [ 3b,12 ] metal‐enhanced singlet oxygen generation (ME‐SOG), [ 3b,13 ] and surface‐enhanced Raman scattering (SERS) [ 3b,14 ] applications.…”
Section: Introductionmentioning
confidence: 99%